Evaluación de estrés en los estudiantes del tercer ciclo de la Carrera de Medicina de la Universidad Nacional de Loja - Valverde Encalada, José Luis (2015)
This investigative work had as main objective assess academic stress; as well as determining the conditions socio-demographic of each one of the students of the third cycle of Medicine of the Universidad Nacional de Loja; and at the same time to establish if there is relationship between these variables and the generation of academic stress. Is a study of transverse type, with a descriptive approach, the academic stress evaluation questionnaire (EAEC) (Joan De Pablo, 2002) was used for the collection of the information and to determine the socio-demographic variables, a survey by the author was created, the sample consisted of 90 students who were attending in a way regular to his university activities obtained the following results: Students presented a half in general academic stress. the conditions that generate more stress occur especially in evaluations process i.e. the (93.3%) of the sample studied says to feel very stressed at this time in particular followed by the mandatory approval of materials and time scarce for the study with the 94.4%.y 88.9% respectively. Within the socio-demographic variables: do some kind of work extra class, as well as having children are significant for academic stress is 4.8% of the sample studied says that in some way due to time or pressure for the care of their children the academic activities are interrupted in a way which leads to emotional stress generating academic stress. Keywords: Academic stress, socio-demographic variables, academic activities